Blunted beta-adrenoceptor-mediated inotropy in valvular cardiomyopathy: another piece of the puzzle in human aortic valve disease. (23rd February 2021) - Petersen, Johannes; Kloth, Benjamin; Iqbal, Shahria; Reichenspurner, Hermann; Geelhoed, Bastian; Schnabel, Renate; Eschenhagen, Thomas; Christ, Torsten; Girdauskas, Evaldas
Abstract: OBJECTIVES: Heart failure induced by valvular cardiomyopathy occurs in a substantial proportion of patients undergoing heart valve surgery. We aimed (i) to quantify beta-adrenoceptor (beta-AR) function by measuring the inotropic effect of isoprenaline in left ventricular (LV) tissue and (ii) to correlate beta-AR-mediated inotropy with clinical markers of heart failure. METHODS: A total of 179 LV myocardial samples were obtained from 104 consecutive patients who underwent aortic valve (AV) surgery between 2017 and 2019. Beta-ARs were stimulated by increasing the concentrations of isoprenaline, followed by a single high concentration of forskolin and calcium. Beta-AR sensitivity was estimated as the concentration to achieve half maximum effects (EC50 ). Maximum effect size was calculated as the relative beta-AR-mediated inotropic response compared to the force in the presence of high calcium [FISO/Ca (%)]. In vitro data were correlated with the clinical indicators of LV disease. RESULTS: FISO/Ca was independent of age and sex and amounted to 79.6 ± 20.5%. In a multivariate regression model, we found a significant inverse association between FISO/Ca and preoperative left ventricular end-diastolic diameter increase per 10 mm (OR −9.24, 95% CI −16.66 to −1.82; P  = 0.015). Furthermore, patients with end-stage heart failure showed a strong tendency towards more severe reduction of max beta-AR response, as indicated by reduced FISO/Ca in a multivariate model (OR −29.60, 95% CI −61.92 to 2.72; P  = 0.055). CONCLUSIONS: Our study indicates that in vitro myocardial contractility testing can quantify beta-AR dysfunction in patients with AV disease. We found a significant association between reduced beta-AR sensitivity and increased LV diameter, which may indicate a role of beta-AR dysfunction in the development of heart failure in patients with AV disease.